2018
DOI: 10.3389/fpsyg.2018.02079
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review of School-Based Physical Activity for Enhancing Cognition and Learning: The Importance of Relevancy and Integration

Abstract: Engaging in regular physical activity can have substantial cognitive and academic benefits for children, and is generally promoted for its beneficial effects on children’s physical and mental health. Although embodied cognition research has convincingly shown the integral relationship of the human body and mind, in schools physical activity and cognitive activity are typically treated as unrelated processes. Consequently, most physical activities used are neither sufficiently relevant for nor fully integrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 182 publications
2
71
0
13
Order By: Relevance
“…Previous research found no differences between active breaks and traditional seated lessons on mathematics performance (22), on-task behaviour or sustained attention in primary school children (24). Possibly, longer activity breaks around 10 minutes or even physically active lessons, involving adjusted lessons with physical activities integrated with the academic instruction, would be able to fully engage students to the academic curriculum and enhance their on-task behaviour and academic performance (22,25,26).…”
Section: Discussionmentioning
confidence: 95%
“…Previous research found no differences between active breaks and traditional seated lessons on mathematics performance (22), on-task behaviour or sustained attention in primary school children (24). Possibly, longer activity breaks around 10 minutes or even physically active lessons, involving adjusted lessons with physical activities integrated with the academic instruction, would be able to fully engage students to the academic curriculum and enhance their on-task behaviour and academic performance (22,25,26).…”
Section: Discussionmentioning
confidence: 95%
“…Thus these activities may bring psychological and physiological benefits (e.g. health promotion, feelings expression, formation of critical awareness, autonomy development, and motivation for study, among others) (Munoz et al, 2004;Pettersson, 2000;Sarma, 2017;Mavilidi et al, 2018 Physical activity can be carried out without restriction by the deaf population.…”
Section: Benefits Of Physical Activity For Deaf Childrenmentioning
confidence: 99%
“…To date, there are two scientific consensus statements on the effect of physical activity and aging, and cognitive and academic performance [26,42]. Regarding aging, twenty-six researchers from nine different countries and a variety of academic disciplines met in Denmark to reach an evidence-based consensus about physical activity and its effect on older adults.…”
Section: Scientific Consensusmentioning
confidence: 99%
“…We further distinguish between acute and chronic effects of physical activity. Acute effects develop during short-term exposure or a single bout of physical activity, whereas repeated bouts of physical activity are needed for the chronic effects to take place [26]. Both effects are significant, with acute effects, on one hand, expressed as improved attention and cognitive function [13,26].…”
Section: Current Studymentioning
confidence: 99%
See 1 more Smart Citation